(NnEKOTORYE PROBLEMY ORKESTROWKI(B.s (NnAPRQVENNOSTX ORKESTROWOGO TEMBRA I ORKESROWAQ DINAMIKA(B.s - (Ni(B.(Nb(B.(NfINKELX[TEJNs ((NmOSKWAs (NmUZYKAs, 1964)
(NnA \TOM SWOJSTWE ORKESTROWKI OSNOWANA W ^ASTNOSTI(B.s
Keywords: (NtEORIQ(B.s